2008
DOI: 10.1017/s1355617708080284
|View full text |Cite
|
Sign up to set email alerts
|

Visual hemispatial neglect, re-assessed

Abstract: Increased computer use in clinical settings offers an opportunity to develop new neuropsychological tests that exploit the control computers have over stimulus dimensions and timing. However, before adopting new tools, empirical validation is necessary. In the current study, our aims were twofold: to describe a computerized adaptive procedure with broad potential for neuropsychological investigations, and to demonstrate its implementation in testing for visual hemispatial neglect. Visual search results from ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 24 publications
(28 reference statements)
4
61
2
Order By: Relevance
“…It has been repeatedly demonstrated that patients with minimal evidence of neglect on traditional measures (like typical cancelation and line bisection tasks used to assess patients in the present investigation) nonetheless exhibit notable impairments in more precisely controlled adaptive computerized tasks, such as conjunctive search (e.g., List et al, 2008) and dual-task paradigms (e.g., Bonato et al, 2013) simulating attentional demands more similar to those of real-world interactions. Furthermore, as previously noted, visual neglect also involves a fundamental loss of attentional capacity throughout the visual field (for reviews, see Robertson, 2001; Husain and Rorden, 2003).…”
Section: Methodsmentioning
confidence: 59%
“…It has been repeatedly demonstrated that patients with minimal evidence of neglect on traditional measures (like typical cancelation and line bisection tasks used to assess patients in the present investigation) nonetheless exhibit notable impairments in more precisely controlled adaptive computerized tasks, such as conjunctive search (e.g., List et al, 2008) and dual-task paradigms (e.g., Bonato et al, 2013) simulating attentional demands more similar to those of real-world interactions. Furthermore, as previously noted, visual neglect also involves a fundamental loss of attentional capacity throughout the visual field (for reviews, see Robertson, 2001; Husain and Rorden, 2003).…”
Section: Methodsmentioning
confidence: 59%
“…The 2AFC procedure is generally considered to be less affected by bias than the yes-no task and provides relatively simple data for analysis, though it is made less efficient by the requirement for two observation intervals, as opposed to one. Several researchers have used the SIAM YN task in areas such as visual feature search with hemineglect patients (Brooks, Wong, & Robertson, 2005;List et al, 2008), brightness matching (Brown & Rudd, 1998), and auditory filter measurements (Leeuw & Dreschler, 1998). However, 20 years have passed since the description of the SIAM YN task was published (i.e., since Kaernbach, 1990b), and these studies appear to be the only reported use of the SIAM task.…”
mentioning
confidence: 99%
“…The conjunction search requires observers to search for a target object (e.g., red square) among a display of 13 or 14 distractors that are either the same color or the same shape as the target object (e.g., red triangles and blue squares, see List et al, 2008 for a more complete description). The participants were instructed to look at the fixation cross in the center of the screen at the beginning of each trial, and then to verbally indicate whether the target was present or not by verbalizing “yes” or “no”.…”
Section: Methodsmentioning
confidence: 99%
“…The initial display duration was set at 2000 ms and we manipulated the display duration to reach an adjusted accuracy rate of 75% (further details of this procedure are provided in List et al, 2008). Staircases terminated after 10 reversals (when the answer from one trial to the next went from correct to incorrect or vice versa).…”
Section: Methodsmentioning
confidence: 99%